2011
DOI: 10.1089/hum.2010.090
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Pro-opiomelanocortin Expression Induces Melanogenic Differentiation and Inhibits Tumor Angiogenesis in Established Mouse Melanoma

Abstract: Malignant melanoma is one of the leading causes of cancer mortality worldwide, underlining the need for effective novel therapies. In this study, the therapeutic efficacy and mechanism of systemic pro-opiomelanocortin (POMC) therapy were evaluated in mice bearing established melanoma. Injection of adenovirus encoding POMC (Ad-POMC) led to hepatic POMC overexpression and elevated adrenocorticotropin (ACTH) levels in the circulation. Systemic POMC therapy significantly attenuated the growth of established melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
5
21
0
Order By: Relevance
“…Our previous studies showed that POMC gene transfer disrupted the angiogenic processes of cultured endothelial cells (31,37) and primary tumor neovascularization through a-MSH signaling pathway (21). In the present study, we further showed that systemic POMC therapy elicited the neovascularization blockade in metastatic melanoma by using fluorescent dye tracking and CD31 immunostaining.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Our previous studies showed that POMC gene transfer disrupted the angiogenic processes of cultured endothelial cells (31,37) and primary tumor neovascularization through a-MSH signaling pathway (21). In the present study, we further showed that systemic POMC therapy elicited the neovascularization blockade in metastatic melanoma by using fluorescent dye tracking and CD31 immunostaining.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, exogenously supplied HDGF studies confirm that HDGF expression directly regulates the invasion and EMT of melanoma cells. Together with our early studies showing that POMC therapy suppresses melanoma through MC1R/NFkB signaling and angiogenesis inhibition (20,21), we herewith provide a hypothetical model for POMC-induced metastasis suppression through HDGF depletion, which leads to EMT perturbation, and angiogenesis inhibition (Fig. 5D).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Murine models of inflammatory bowel disease showed that disease activity and tissue injury were suppressed by antiangiogenic agents or genetic overexpression of soluble VEGFR-1 (which is inhibitory in nature) and exacerbated by administration or genetic overexpression of VEGF-A [20]. In vivo studies have also demonstrated that pro­opiomelanocortin gene delivery reduced tumor angiogenesis in melanoma models [21]. …”
Section: α-Melanocyte-stimulating Hormonementioning
confidence: 99%